Pengaruh Transformational Leadership terhadap Job Satisfaction yang dimediasi Oleh Occupational Self-Efficacy - Galuh Adhiyaksa; Suhana (Bandung Conference Series: Psychology Science, 2024)
Abstract. The work environment directly impacts job attitudes, particularly job satisfaction, which refers to one's attitude toward their job. Several studies have shown that organizations can enhance their employees' job satisfaction through transformational leadership. Job satisfaction is associated with the level of self-efficacy, known as occupational self-efficacy in the job context. Occupational self-efficacy can empower employees to navigate various changes in their work conditions. Among the many changes that have occurred, the most comprehensive change is the transition from traditional office work to remote work. The aim of this research is to investigate the influence of transformational leadership on job satisfaction among remote workers at PT. X, mediated by occupational self-efficacy. The research design employed in this study is a quantitative and causal approach. The study involved 16 employees at PT. X. The measurement tool used to assess transformational leadership is the Multifactor Leadership Questionnaire (MLQ) developed by Bass and Avolio (1995) and adapted by Akbar (2011), with a Cronbach's alpha value of 0.960. Job satisfaction is measured using the Job Satisfaction Scale (JSS) developed by Spector (1997) and adapted by Akbar (2011), with a Cronbach's alpha value of 0.964. Occupational self-efficacy (OSS) is measured using Bandura's (2010) scale, adapted by Rubianto & Kembaren (2023), with a Cronbach's Alpha value of 0.897. The research findings indicate that transformational leadership has an indirect and non-significant influence on job satisfaction, accounting for 16.3%. Abstrak. Lingkungan kerja berdampak langsung pada sikap kerja, sikap terhadap penilaian di pekerjaan disebut job satisfaction. Dalam beberapa penelitian menunjukan bahwa organisasi dapat meningkatkan job satisfaction karyawannya, dengan transformational leadership. Job satisfaction berhubungan dengan tingkat self-efficacy, pada latar pekerjaan disebut occupational self-efficacy. Occupational self-efficacy dapat membuat karyawan mengatasi setiap perubahan kondisi kerja. Diantara sekian banyak perubahan yang terjadi, perubahan yang paling menyeluruh adalah peralihan pekerjaan secara langsung menjadi remote work. Tujuan penelitian ini dilakukan untuk mengetahui pengaruh Transformational leadership terhadap Job satisfaction pada Karyawan Remote work di PT. X yang dimediasi oleh occupational self-efficacy. Desain penelitian yang digunakan dalam penelitian ini adalah pendekatan kuantitatif dan kausalitas. Subjek penelitiannya sebanyak 16 karyawan di PT. X. Alat ukur yang digunakan untuk mengukur transformational leadership adalah skala Multifactor Leadership Questionnaire (MLQ) milik Bass dan Avolio (1995), yang telah diadaptasi oleh Akbar (2011) nilai Cronbach’s alpha 0.960. Alat ukur job satisfaction menggunakan Job Satisfaction Scale (JSS) milik Spector (1997) yang diadaptasi oleh Akbar (2011) nilai Cronbach’s alpha 0.964. Alat ukur occupational self-efficacy (OSS) milik Bandura (2010) yang diadaptasi oleh Rubianto & Kembaren (2023) nilai Cronbach’s Alpha 0.897. Hasil penelitian menunjukan bahwa transformational leadership tidak berpengaruh signifikan terhadap job satisfaction secara tidak langsung sebesar 16,3%.